2022
DOI: 10.1186/s12909-022-03965-9
|View full text |Cite
|
Sign up to set email alerts
|

Development, outcome and costs of a simulation-based neurosurgery bootcamp at the national level

Abstract: Introduction With a growing interest in simulation-based training to develop clinical proficiency, bootcamps have been utilized for imparting basic skills to medical trainees. While considerable research on the topic exists in high income countries, no such neurosurgical teaching standards have been employed in Low- and Middle-Income Countries. Methods We conducted a cross-sectional study to explore the effectiveness of first low-cost, multi-center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…Among these, four gave the maximum score, while 71.4% considered it essential. In a concurrent investigation, Bakhshi et al (2022) reported that, among the 22 apprentices evaluated, only one (4.55%) had previously participated in a neurosurgical skills workshop [ 20 ]. This scenario reiterates the observation that, although training in 3D simulators is accessible and low-cost, it is a rarity in neurosurgery residency programs, despite representing a response to a need identified by residents around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, four gave the maximum score, while 71.4% considered it essential. In a concurrent investigation, Bakhshi et al (2022) reported that, among the 22 apprentices evaluated, only one (4.55%) had previously participated in a neurosurgical skills workshop [ 20 ]. This scenario reiterates the observation that, although training in 3D simulators is accessible and low-cost, it is a rarity in neurosurgery residency programs, despite representing a response to a need identified by residents around the world.…”
Section: Discussionmentioning
confidence: 99%